A Peculiar Case of Large and "Unresectable" Primary Localized Cutaneous Nodular Amyloidosis of the Ankle - Antonio Stanizzi; Matteo Torresetti; Francesca Barbisan; Benedetta Peltristo; Yasmine Zavalloni; Giovanni Di Benedetto (Karger Publishers, 2021)
Nodular cutaneous amyloidosis represents the rarest variant of primary localized cutaneous amyloidosis. The proposed management ranges from topical or systemic agents to surgical treatment. Complete surgical excision is advisable due to its potential progression to systemic amyloidosis due to dermis and subcutaneous tissue infiltration. However, in particular locations, the risk of functional complications is high, so an alternative treatment option should be considered. We report a case of a large primary nodular cutaneous amyloidosis of the leg involving the joint capsule which was successfully treated by incomplete surgical removal, without recurrences at 7-year follow-up.